Analisis Ikon Indeks dan Simbol dalam Ritual Hulla Poddu pada Masyarakat Sumba Barat - Kamuri, Paulus Ama; Gena, Engel B. H.; Kelen, Konradus D.; Kami, Kanisius; Bayo, Hendro (Indo-MathEdu Intellectuals Journal, 2026)
The Hulla Poddu ritual is a sacred practice of the people of West Sumba that represents the relationship between humans, nature, and ancestors within the Marapu belief system. This study aims to uncover the semantic structure of icons, indices, and symbols in this ritual through Charles Sanders Peirce’s semiotic approach. A descriptive qualitative method was applied using triadic analysis. The results of the study indicate that icons are manifested in offerings of agricultural products such as corn, rice, sweet potatoes, betel, and areca nuts, as well as ritual attributes including water, kitchen ash, coconut shells, star-shaped woven coconut leaves, and ritual movements such as pounding rice or swinging a machete. Indexes are identified through the sounds of gongs and drums as the ritual’s opening markers, the blood of sacrificial animals chickens, pigs, buffalo, and horses customary prohibitions, and the smoke from burning offerings, which signify a causal connection with ancestors. Symbols are constructed through the kataga incantations recited by the Rato Marapu, sacrificial animals, traditional black attire, and the Hulla Poddu as the “sacred month,” which establishes a performative collective sacredness. These findings affirm the ritual as a living, contextual cosmological sign system, offering a theoretical contribution to the understanding of the semiotics of agrarian rituals in Eastern Indonesia.